Liquidity In Its Influence On Tax Aggressiveness - Nurfadillah, Ceri Febriani; Achmad Subagdja; Syahrudin, Muhammad (Journal of Accounting Inaba, 2024)
Indonesia is a developing country with rapid economic growth. One of the biggest sources of state revenue today is tax. Many cases of tax aggressiveness have occurred in Indonesia, even to the detriment of the state with a fantastic amount of money. This study aims to examine the effect of liquidity, measured using the current ratio (CR), on tax aggressiveness, measured using the effective tax rate (ETR). The research method used is quantitative with an associative descriptive analysis approach. The population consists of 78 consumer goods industry manufacturing companies, with a research sample of 23 companies and a total of 92 data points. The data analysis technique used is panel data regression analysis with estimation through the Random Effect Model (REM), tested using Eviews 12 software. The results showed that the level of liquidity does not have a significant effect on tax aggressiveness, this is evidenced based on the hypothesis test that has been carried out